PATIENT SATISFACTION OF DENTAL SERVICES IN BANJARMASIN DURING THE COVID-19 PANDEMIC - Ika Kusuma Wardani; Erika Norfitriah; Renie Kumala Dewi (FKG Unlam, 2022)
Background: A public health center is one of the primary health services that is obliged to provide health services during the covid-19 pandemic. At that period, dentists in the public health center must continue to provide services to patients according technical instructions. Changes in the service system during the pandemic has different perceptions of service quality which had an impact on patient satisfaction. Objective: The purpose of this study was to describe patient satisfaction of dental services in Banjarmasin during the covid-19 pandemic. Methods: This research is descriptive with a cross-sectional design. The population in this study were all people who came to the dental service of the public health center in Banjarmasin. The number of samples in this study was 86 samples taken by accidental sampling. Results: The results of this study showed that the reliable dimension there was 42 person (49%) who said reliable dimension is very satisfied, 52 person (61%) who said assurances dimension is very satisfied, 42 person (49%) who said tangible dimension is very satisfied, 43 person (50%) who said empathy dimension is very satisfied, and 53 person (61%) who said responsiveness dimension is very satisfied. Conclusion: It can be concluded that most patients are very satisfied with the health services provided by dentists in public health center Banjarmasin during the covid-19 pandemic because most of them applied service quality with 5 dimensions (assurance, empathy, reliable, responsiveness and tangible). Keywords : Assurance, Emphaty, Reliable, Responsiveness, Tangible.